The secondary metabolites profile of Stemphylium lycopersici, the causal agent of tomato grey leaf spot, is complex and includes host and non-host specific toxins - Medina, Rocío (2021)
The aim of this work was to characterize the secondary metabolite (SMs) profile of Stemphylium lycopersici, a necrotrophic fungus that causes the disease known as grey leaf spot. We detected twenty-four SMs in cultures of S. lycopercisi within the extracts of 19 isolates. Each of them presented a characteristic unique profile. While highly virulent isolates synthesized a high number of metabolites (15), the low virulent ones synthesized a low number of SMs (2). However, a PCA analysis could not establish the relationship between SMs and virulence. Infectopyrone was the most frequent metabolite produced by the isolates (89%).